Comparação entre Reciproc Blue e quatro instrumentos réplicas: aspectos metalúrgicos, geometria, comportamento em torção e flexão - Gustavo Oliveira Campos (2023)
The introduction of NiTi alloy in endodontics has allowed the manufacturing of instruments with excellent mechanical properties, and one of the main characteristics is the ability to change alloy’s transformation temperature, which can enable the presence of martensite at room temperature and consequently favor a shape memory effect. However, some of the currently marketed systems have limited or no scientific information regarding their mechanical properties, design characteristics, and manufacturing methods. The aim of this study was to compare the geometric characteristics, metallurgical aspects, and mechanical properties (torsional and flexural strength) of Reciproc Blue instruments (VDW, Munich, Germany) with four replica-like reciprocating systems. A total amount of 39 instruments from each reciprocating system, namely Reciproc Blue (RB), Prodesign R (PDR), V File (VF), V+ File (V+), and Univy One (UO), were used in the study. The Image J program was used to measure the diameters at every millimeter along the instruments active portion and the cross-sectional area at 3 mm from the instrument tip. SEM images of the active portion were obtained to evaluate the surface finishing of the instruments. Atomic composition, phases present, and transformation temperatures were determined through EDS, XRD, and DSC analyses, respectively. Flexibility was assessed by bending tests up to 45° according to ISO 3630-1 specifications, and torsional strength tests were performed according with ANSI/ADA Specification No. 28. All instruments exhibited an approximately equiatomic composition of nickel and titanium. Qualitative analysis of the crystalline phases using XRD tests demonstrated the predominance of the R-phase in all groups, except for the UO group, which exhibited a mixture of R-phase and B19' martensite. In terms of diameter and cross-sectional area evaluation, the RB instrument obtained intermediate values, while the PDR and V+ instruments had smaller values, and the VF and UO instruments had larger values. A significant impact of geometry on mechanical properties was observed, with systems exhibiting a smaller area than RB (PDR, V+) being more flexible and less torsion-resistant (p<0.05), and the VF instrument with a larger area showed, as expected, less flexibility (p<0.05) and similar torsional resistance (p>0.05). The only exception was the UO system, which, despite having a larger geometric configuration, exhibited greater flexibility and less torsional resistance, likely due to the higher amount of martensite present at room temperature. None of the replica-like instruments evaluated showed identical characteristics and mechanical behavior to the standard RB system. Further studies are suggested to compare the clinical performance of these instruments.